Improvements in Agriculture in Ricardo's Essay on Profits - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 1993)
Although Ricardo abstracted from improvements in agriculture in the basic model which he developed his Essay on Profits to make a defense for free trade, he nevertheless quite frequently made reference to some results of improvements in agriculture. Ricardo upheld 2 consequences that would theoretically result from improvements in agriculture: 1. the relative price of corn must decline, and 2. consequently, the rate of profit would rise. Although these theoretical results follow from an implicit model which Ricardo had in mind, he made it clear that, in practice, he did not believe that the escape from the stationary state would be likely to come from improvements in agriculture. An attempt is made to develop a model of improvements in agriculture taking the form of technological advance in their intermediate (fertilizer) input sector in the context of Ricardo's Essay on Profits model and to ask what the implications are for long-run growth and income distribution.